Penggunaan Media Berbasis Sistem Informasi Geografis untuk Meningkatkan Kecerdasan Spasial dalam Pembelajaran - Wenty Nores Kartadireja; Lili Somantri; Nanin Trianawati Sugito (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2024)
Spatial intelligence is a person's ability to describe a phenomenon in terms of spatial concepts. In learning geography, spatial intelligence is needed to make it easier for students to visualize every phenomenon. However, the level of spatial intelligence of each individual is different, so it needs to be supported with the right media in learning. The purpose of this study was to analyze the effectiveness of Geographic Information System-based media in improving spatial intelligence. The method used is quantitative with a t-test and N-Gain test. The results obtained t value (56) = 2.982, p = 0.004, the significance value of 0.004 <0.05, and t count (2.982) > t table (2.048) means that there is a significant difference between the control class and the experimental class. The control class N-Gain test obtained a value of 0.15 (low category) while the experimental class was 0.34 (medium category), meaning that the experimental class was more effective than the control class. Based on these results, using the right media can improve students' spatial intelligence in learning.